FORMATION OF THE ARMED FORCES IN UKRAINE AND THE BALTIC STATES IN THE FIRST DECADE OF RESTORED INDEPENDENCE (Південний архів (історичні науки), 2023)
This article provides an overview of the formation of the armed forces in Ukraine and the Baltic countries during the first decade of their restoration of independence. It states that since these countries declared their independence at the end of the summer of 1991, it was necessary to form their own armies to maintain it. Considering that this the process takes quite a long time, so starting from the fall of 1991, the armed forces of these countries are undergoing formation and transformation. The purpose of the article is to analyze the process of formation of the armed forces in Ukraine and the Baltic states in the first decade of their restoration of independence. During the study of the formation of the armed forces in Ukraine and the Baltic states, the following methods were used: historical-comparative, idiographic, analysis, synthesis and dynamics. The results. This article notes that Ukraine based its new army on the former Soviet heritage, while the Baltic states abandoned this and began to form their own armed forces from a «clean sheet». However, already in the first months of independence, Russia began to promote the demilitarization of Ukraine. The Ukrainian government interacted both with NATO member countries and with the CIS countries, which did not contribute to the qualitative reform of the Armed Forces of Ukraine. The Baltic countries, in the first years of regained independence, took a course for close cooperation with NATO and later acquired membership in this Organization. If the Ukrainian leadership from the very beginning of independence paid more attention to the armed forces, then later it reduced the expenses for its maintenance in the conditions of the economic crisis. The Baltic countries, on the contrary, began to increase spending and increase their armies at the end of the 1990s. in terms of the course to NATO. The political elite of the Baltic countries was more ideologically monolithic and far-sighted than the Ukrainian one, which was also reflected in the issue of national security and the strengthening of the armed forces. Conclusions. Therefore, the process of formation of the armed forces in Ukraine and the Baltic countries was influenced by internal (maturity of the political elite, state of the economy, Soviet legacy, etc.) and external (potential risks of a new occupation, strengthening of Russia and its geopolitics towards its neighbors, NATO expansion, etc.) factors.
Keywords: servicemen, army, troops, navy, independence, security, law